2006
DOI: 10.1111/j.1601-5215.2006.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influences on first-episode admission in affective and non-affective psychosis

Abstract: Background: Since bipolar affective disorder has been recorded, clinicians treating patients with this disorder have noted the cyclic nature of episodes, particularly an increase in mania in the spring and summer months and depression during winter. Objective: The aim of this study was to investigate seasonality in symptom onset and service admissions over a period of 10 years in a group of patients (n ¼ 359) with first-episode (FE) mania (n ¼ 133), FE schizoaffective disorder (n ¼ 49) and FE schizophrenia (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
(63 reference statements)
1
8
0
Order By: Relevance
“…However, the results point to a peak of such admissions during the summer months (Whitney et al, 1999;Cassidy and Carroll, 2002), as well as in early spring (Lee et al, 2007). Also, different patterns of seasonality of admissions depending on the sex of bipolar patients have been reported (Kerr-Correa et al, 1998;Hallam et al, 2006). For example, Kerr-Correa et al, (1998) found in their study that the seasons influenced only manic episodes and only among women and mostly in the spring and summer.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the results point to a peak of such admissions during the summer months (Whitney et al, 1999;Cassidy and Carroll, 2002), as well as in early spring (Lee et al, 2007). Also, different patterns of seasonality of admissions depending on the sex of bipolar patients have been reported (Kerr-Correa et al, 1998;Hallam et al, 2006). For example, Kerr-Correa et al, (1998) found in their study that the seasons influenced only manic episodes and only among women and mostly in the spring and summer.…”
Section: Introductionmentioning
confidence: 79%
“…For example, Kerr-Correa et al, (1998) found in their study that the seasons influenced only manic episodes and only among women and mostly in the spring and summer. On the other hand, Hallam et al (2006) pointed out that seasonal changes can flare up affective disorders (mainly bipolar disorder), especially among male patients. One can also find studies where no link has been found between the seasons and the frequency of admission of affective disorder patients to hospitals (Daniels et al, 2000).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The long‐standing hypothesis that symptoms of bipolar disorder (BD) vary systematically with the seasons has significant implications. Evidence for seasonal variation would support a role for light and biological rhythms in BD (1) and predictable seasonality could facilitate relapse prevention and service planning (2). However, existing research is equivocal about seasonality in BD, and the overarching aim of this study was to move towards a more definitive conclusion.…”
Section: The Present Studymentioning
confidence: 99%
“…A similar relationship exists between MS relapse rates and latitude, with rates increasing further from the equator [4]. An association has been observed between season and first-break schizophrenia and psychosis, with a stronger effect in males [5,6]. Seasonal rhythms in gene expression have been found to be interrupted by Alzheimer's disease [7].…”
Section: Introductionmentioning
confidence: 73%